High seas in the cloud: the role of big data and artificial intelligence in support of high seas governance – The Sargasso Sea pilot - David Freestone; Kieran N. Bjergstrom; Kristina M. Gjerde; Patrick Halpin; Kevin P. Fleming; Andrew Hudson; Alex D. Rogers; Fae Sapsford; Vardis M. Tsontos; Jorge Vazquez-Cuervo; David Vousden (Frontiers in Marine Science, 2024)
This article examines the future governance of areas beyond national jurisdiction (ABNJ) in the wake of the new 2023 United Nations Agreement using the work on the Sargasso Sea as a prototype. After discussing the legal framework and current challenges facing the ABNJ regime, some details are provided on open ocean data collection technologies, including big data and artificial intelligence (AI), used in support of ocean governance. Based on a technology-enabled ocean governance cycle, the role that data, information technology and data-science can play in incorporating empirical scientific knowledge into policy and decision-making is examined with a focus on the open ocean. The article concludes with a vision of future high seas governance based on the 2023 Agreement and how big data and AI can play a crucial role in meeting the exciting challenges that the new agreement poses.

A role for artificial night-time lighting in long-term changes in populations of 100 widespread macro-moths in UK and Ireland: a citizen-science study - John Fawcett Wilson; David Baker; Janet Cheney; Mike Cook; Martin Ellis; Roger Freestone; David Gardner; Graham Geen; Robin Hemming; Don Hodgers; Stephen Howarth; Ade Jupp; et al. (Journal of Insect Conservation, 2018)

Climate association with fluctuation in annual abundance of fifty widely distributed moths in England and Wales: a citizen-science study - John Fawcett Wilson; David Baker; Mike Cook; George Davis; Roger Freestone; David Gardner; Dave Grundy; Norman Lowe; Steve Orridge; Heather Young (Journal of Insect Conservation, 2015)